Adolescent Callous-Unemotional Traits and Parental Knowledge as Predictors of Unprotected Sex Among Youth. (January 2016) - McCauley, Katherine Long; Shadur, Julia Madeline; Hoffman, Elana Michelle; MacPherson, Laura; Lejuez, C. W.
Risky sexual behavior among adolescents is common and results in many negative consequences. The present study investigated longitudinal predictors of adolescents' likelihood of engaging in unprotected sexual intercourse. Parental knowledge, or the extent to which parents know about their children's activities, whereabouts, and friendships, is a robust predictor of youth risk behavior, including risky sexual behavior. However, parenting practices are typically less potent as predictors of subsequent behavior among youth with high levels of callous-unemotional (CU) traits. We conducted three logistic regression models, each of which examined parental knowledge in a different way (through child report, parent report, and a discrepancy score), allowing us to examine parental knowledge, CU traits, and their interaction as predictors of adolescents' subsequent engagement in sex without a condom. Results indicated that adolescents who perceived their parents to possess greater knowledge were less likely to engage in unprotected sex. Higher parent report of parental knowledge was also related to decreased likelihood of engaging in unprotected sex, but only for adolescents with high levels of CU traits. In addition, greater discrepancy between parent and adolescent reports of parental knowledge was related to increased likelihood of engaging in unprotected sex, but only for adolescents with low levels of CU traits. Results highlight the importance of considering both parent and adolescent perceptions of parental knowledge and have important implications for prevention and intervention efforts.